Analysis Of The Effect Of Internal Locus Of Control And Need For Achievement On Entrepreneurial Intention Through Entrepreneurial Attitude In Vocational High School Students - Priyono, Ahmad; Ludi Wishnu Wardana; F. Danardana Murwani (International journal of technology and education research, 2025)
This study aims to analyze the influence of internal locus of control and need for achievement on entrepreneurial intention with entrepreneurial attitude as a mediating variable among vocational high school (SMK) students. The background of this study stems from the need to strengthen students' psychological factors in an effort to foster entrepreneurial spirit and prepare SMK graduates to be able to create business opportunities independently. This study uses a quantitative approach with an explanatory design. The population consists of 210 students in the 12th grade of the Marketing Program from four SMKs in Malang City, while 131 students were sampled using proportional random sampling. Data were collected using a Likert scale questionnaire that had undergone validity and reliability tests. Data analysis was performed using path analysis with LISREL 8.8 to identify the direct and indirect effects between variables. The results showed that internal locus of control had a positive and significant effect on entrepreneurial attitudes. Similarly, the need for achievement was found to have a positive and significant effect on increasing students' entrepreneurial attitudes. Both variables also had a positive and significant effect on entrepreneurial intention. Entrepreneurial attitude was found to have a positive and significant effect on entrepreneurial intention and to act as a partial mediator in the relationship between internal locus of control and need for achievement with entrepreneurial intention. These findings indicate that psychological factors and individual attitudes play an important role in encouraging entrepreneurial intentions among vocational high school students. Therefore, strengthening entrepreneurship education needs to focus on developing students' character, motivation to achieve, and self-confidence to dare to start a business